Implementasi Integrasi-Interkoneksi pada Pembelajaran Ulumul Hadits di Program Studi Sosiologi UIN Sunan Kalijaga Yogyakarta - Muhammad Nur Hafidz Afif; Eva Latipah; Yayan Suryana (MANAZHIM, 2022)
Lecturers/educators in learning have a vital role, especially in building the integration-interconnection paradigm in students. Lecturers/educators must be able to bridge students by combining religious knowledge and general science. This paper aims to determine how the implementation of integration-interconnection in Ulumul Hadith learning at the Sociology Study Program of UIN Sunan Kalijaga Yogyakarta. The research method in writing this article uses a qualitative research type. This study collects data from the field by producing descriptive data in words or verbal (narrative). Data were collected through active participation observation and documentation methods. The approach used is phenomenological. The collected data will be analyzed using the Miles and Huberman analysis model, namely data reduction, display, and conclusion. This study found that integration-interconnection in Ulumul Hadith learning has been formulated by lecturers/educators in RPS. As for its application in integration-interconnection learning is implemented in five levels, namely the philosophical level, the level of research methods and approaches, the material level, the strategy level, and the evaluation level. In general, integration and interconnection in Ulumul Hadith learning in the Sociology Study Program has been implemented.